Korean practices and challenging issues in regulatory impact analysis - Lee, Jongyearn (Improving Regulatory Governance: Trends, Practices and the Way Forward, 2017)
This chapter looks at the different practices and experience of Korea in designing and implementing regulatory impact assessments (RIA). It provides a comprehensive account of the history and evolution of its adoption and implementation and focuses on the different methodological issues and challenges in managing and undertaking RIA. First, if a target or budget is adopted, it should focus on net (value) impact on business, though the impact on the wider economy and society should not be neglected. Second, while reviews of the stock are helpful, estimating the size of the stock is fraught with conceptual and practical difficulties. Third, RIAs should be integrated with the policy development process and not considered as an “add-on”. Fourth, RIAs should also inform decisionmaking and scrutiny by Parliament and not just be a process for the Executive. Finally, there is plenty of scope to improve benefit modelling and to consider alternatives to CBA.